Political Participation of the Homeless in Brazil - Baumgarten, B. (CIES Working Papers, 2014)
Most researchers regard the mobilization of the m ost deprived as a rare case that needs further explanation. In this contribution the Brazilian National Movement of the Homeless (Movimento Nacional População Rua – MNPR) will be analysed to show mechanisms of mobilization of the most deprived. Unlike other rare cases of homeless mobilization, the movement is active beyond the local level; it has existed for almost a decade, gaining access to and impact ing on politics at all levels. How does the MNPR attract homeless people and keep them as active participants and leaders? The case study of the MNPR is based on interviews with leaders of the movement and participant observation in São Paulo, Salvador de Bahia and Brasília in 2013.